2011
DOI: 10.1007/s00464-011-1856-1
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous pyogenic liver abscess and acute cholecystitis: how to recognize it and what to do (emergency cholecystostomy followed by delayed laparoscopic cholecystectomy)

Abstract: A simple algorithm is presented for the selection of patients with AC to undergo a CT scan to identify synchronous PLA. Emergency CS followed by delayed LC is a viable, first-line treatment option for synchronous PLA and AC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 28 publications
(44 reference statements)
0
16
0
Order By: Relevance
“…Elective cholecystectomy after cholangitis treatment is a feasible option as per Tokyo guidelines [16]. Other studies showed that drainage followed by delayed surgery is an acceptable treatment for cholecystitis concomitant with liver abscess [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Elective cholecystectomy after cholangitis treatment is a feasible option as per Tokyo guidelines [16]. Other studies showed that drainage followed by delayed surgery is an acceptable treatment for cholecystitis concomitant with liver abscess [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Several risk factors for PLAs, except for biliary disease have been identified, such as cirrhosis, diabetes mellitus, liver transplantation and malignancy. Diabetes mellitus has been estimated to complicate the clinical course of half of the patients that are treated for PLA and in need of treatment in an intensive care unit [1,41].…”
Section: Discussionmentioning
confidence: 99%
“…A pyogenic liver abscess (PLA) is a rather rare entity with an increasing level of occurrence in western countries ranging from 1.1/100,000 to 3.6/100,000 people, and a substantial mortality rate which is estimated to be between 5.6 and 10%. Mortality may even reach 22% when there are multiple PLAs [1,2]. The formation of a PLA is associated with cholelithiasis in as many as 15% of patients and with biliary disease in general in up to 21.9% of patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pyogenic abscesses may be bacterial or fungal. They often can be attributed to bacterial infections of the biliary tree such as cholangitis,9 or more distally in the body such as diverticulitis or inflammatory bowel disease,10 where infection may migrate to the liver via the portal vein system. Bacterial endocarditis, dental infections, fungal infections, cirrhosis,11 blunt trauma12 and foreign bodies13 are other causes.…”
Section: Discussionmentioning
confidence: 99%